The use of information technology in the design of upholstered furniture - Saparbek Әділет (Рroblems of engineering and professional education, 2024)
The article discusses the relevance of using modern information technologies in connection with high requirements for speed and flexibility in the design of upholstered furniture. Specialized software allows you to speed up the development process, optimize it, and create detailed sketches of future products. The introduction of 3D modeling and virtual reality (VR) opens up new opportunities for the furniture industry. The advantages of using modern technologies such as 3D modeling and virtual reality (VR) in furniture design were discussed. These methods allow designers to create a realistic representation of the product, check its compliance with ergonomic requirements and easily adjust design solutions. When designing furniture, special attention is paid to its functional and aesthetic characteristics, ergonomic requirements play an important role. The article presents three-dimensional models of upholstered furniture products created in 3D Max and their virtual placement in the interior. The use of these technologies simplifies all stages of design, eliminates errors and allows you to create products that fully meet the needs of consumers. Models created with the help of information technology save time and money, improve product quality, and also allow to fully satisfy the convenience and aesthetic requirements of the consumer.